Awareness of operators on the requirements and procedures for animal quarantine and the distribution of temporary animal quarantine stations in Peninsular Malaysia - Abdullah, Ummi Noorhakimah; Hassan, Latiffah; Ong, Bee Lee (Department of Veterinary Services Malaysia, 2016)
Temporary quarantine stations (TQS) are transitory premises that have been approved to facilitate the quarantine of imported live animals in Malaysia. These stations must abide to the standard operating procedures (SOP) for animal quarantine as outlined by the veterinary authority in Malaysia. However, the level of awareness for the quarantine procedures among the TQS operators and managers has not been assessed. This study was conducted to describe the distribution of the TQS in 2012-2013 and the level of awareness among its operators on the quarantine procedures and the fundamental requirements for quarantine establishments. Eight TQS from 25 were selected and operators or managers were interviewed using a questionnaire and the facility was visited. The study found that majority (82.5%) of the TQS operators were aware of the quarantine procedures but the auditors from the veterinary authority revealed vice versa.